KENISCAYAAN KONFLIK DALAM MASYARAKAT DEMOKRASI - Sukri, Sukri (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2016)
Nowadays there is a tendency that seeing conflict in the era of democracy as a negative excesses of the existence of democracy. The assumption that democracy is a good system and will bring good for human life then interpreted by a society without conflict. The understanding seems to mask the fact that freedom and equality of each individual offered by the democratic system basically means providing space for conflict because of the nature of human beings as creatures who always has a difference. This paper aims to discuss how conflicts tend to be regarded as non-democratic phenomenon as something that is actually reasonable in the context of democracy. Through the election as one of the pillars and the main indicators of democracy that seems to be a criticism of the denial of the conflict as an important element in democratic society.